Guest Editorial Special Issue on 'THz Communications and Networking' - Akyildiz, Ian F.; Kawanishi, Tetsuya; Gerstacker, Wolfgang; Dong, Xiaodai; Babakhani, Aydin (IEEE Journal on Selected Areas in Communications, 2021)
The Special Issue (SI) on ‘THz Communications and Networking’ of the IEEE Journal on Selected Areas In Communications targets presenting the most recent advances with respect to the theoretical foundations and practical implementation of THz wireless communications and networking. This includes approaches related to channel characterization and modeling, modulation, waveform design, and coding, information-theoretic analysis, channel estimation, detection, and equalization, (massive) multiple-input multiple-output (MIMO) communications, and beamforming, beamtracking, and precoding. The SI is aimed at compiling the latest and most significant research advances related to the modeling, design, analysis, and applications of THz wireless communications and networking as outlined above, and at fostering and envisioning new threads and directions in this still-emerging research area. The SI has attracted 49 high-quality submissions from authors based all around the world. All articles within the scope of the SI received at least three independent reviews, and the accepted articles went through at least one revision round.
CRIS-Team Scopus Importer:2021-06-11